REPRESENTATION OF BEAUTY IN THE WARDAH ADVERTISEMENT “IMPACTFUL BEAUTY FOR THE GREATER GOOD” (2024) - Fatmawati, Efa; Rofik, Abdur; Musliadi, Musliadi (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
This research was conducted to analyze the representation of beauty in the Wardah advertisement